An experimental investigation into the ignition and combustion characteristics of single droplets of biochar water slurry fuels in air. (1st January 2017) - Zhu, Mingming; Zhang, Zhezi; Zhang, Yang; Liu, Pengfei; Zhang, Dongke
Highlights: Ignition of single droplets of the biochar water slurry fuels was heterogeneous. Combustion of the biochar slurry fuel droplets follows shrinking size model. Slurries with higher water contents showed higher burning rates. Burning rate was independent of the initial size of the biochar slurry droplets. Abstract: The ignition and combustion behaviour of single droplets of slurry fuels made from a coconut shell biochar and a pine sawdust biochar was experimentally investigated. The two types of biochar water slurry fuels were prepared with water content varying from 50 to 70 wt% and the median size ( D 50 ) of the biochar particles being approximately 10 μm. Single droplets of the slurry fuels with diameters ranging from 0.5 mm to 1.5 mm were suspended on a silicon carbide fibre and burned in air at 1023 K in an electrically heated tube furnace. The ignition and combustion processes of the droplets of the slurry fuels were recorded using a colour CCD camera at 200 fps. The ignition delay time, burnout time and burning rate based on the d 2 law were determined. It was found that the ignition delay time slightly increased first and then decreased as the water content increased from 50 wt% to 70 wt% for the coconut shell biochar slurry fuels and from 60 wt% to 70 wt% for the pine sawdust biochar slurry fuels, indicating that the effect of water content on the ignition delay time was a trade-off between the water evaporation time and the heating time of residual solid after water evaporation. The combustion of residual solid after ignition followed a shrinking sphere model and was controlled by external oxygen diffusion to the outer surface of the residual solid and a shallow region below the outer surface. The burning rate of the residual solid calculated based on the d 2 law ranged from 0.07 to 0.15 mm 2  s −1, which was also independent of the initial droplet size. A slurry fuel with a higher water content showed a slightly greater burning rate as the voids of inter-particles after water evaporation became larger for slurry fuels with higher water contents.